Ankle syndesmosis biomechanical evaluation by shear-waves elastography in healthy young adults: Assessment of the reliability and accuracy of the measurements and definition of a corridor of normality. Issue 8 (December 2022) - Rougereau, Grégoire; Langlais, Tristan; Vigan, Marie; Hardy, Alexandre; Vialle, Raphaël; Marty-Diloy, Thibault; Cambon-Binder, Adeline
Abstract: Background: Aims of this study were: 1/ to evaluate the shear wave speed (SWS) properties of the anteroinferior tibiofibular ligament (AITFL) and the distal interosseous membrane (DIOM) in neutral, dorsal flexion and plantar flexion positions in a cohort of healthy adult volunteers; 2/ to assess the reliability and reproducibility of these measurements. Methods: Both ankles were analyzed by shear wave elastography (SWE) in 20 healthy patients (10 females/10 males) standing on a hinge support with their ankles in neutral, 20° dorsal flexion and 30° plantar flexion positions. Stiffness of AITFL and DIOM was evaluated by SWS measurement. Results: The SWS of AITFL and DIOM were minimal in the plantar flexion position (4.28 m/s [2.65–5.11] and 3.35 m/s [1.69–4.55], respectively). It increased significantly for both ligaments in neutral position (4.69 m/s [3.53–5.71] and 3.81 m/s [1.91–4.74], respectively; p < 0.0001), and reached their maximum values in dorsal flexion (6.58 m/s [5.23–8.34] and 4.79 m/s [3.07–6.19], respectively; p < 0.0001). There was no correlation between each ligament regardless the positions. SWS of AITFL was independent of demographic characteristics analyzed. SWS of DIOM was negatively correlated with height in dorsal flexion (ρ = −0.35; p = 0.03) and in plantar flexion (ρ = −0.37; p = 0.02). Female gender was associated with increased DIOM SWS in neutral (p = 0.005), dorsal flexion (p = 0.003), and plantar flexion (p = 0.001) positions. Moreover, foot morphology (foot arch, hind foot frontal deviation) did not impact AITFL nor DIOM SWS. Inter- and intra-observer measurements were all good or excellent. Conclusion: The AITFL and DIOM, stabilizers of the distal tibiofibular syndesmosis, increase in stiffness while dorsal flexion increases. This study describes a reliable and reproducible protocol to assess their stiffness by SWE, and defines a corridor of normality. Highlights: Anteroinferior tibiofibular ligament (AITFL) and Distal interosseous membrane (DIOM), have their own function. These two structures increase in stiffness while dorsal flexion increases. This study describes a protocol to assess their stiffness by Shear Wave Elastography, and defines a corridor of normality.